Development of a Patient-Reported Outcomes Measurement Information System (PROMIS®) short form for measuring physical function in geriatric rehabilitation patients. - Smit, E. B.; Bouwstra, H.; van der Wouden, J. C.; Hertogh, C. M. P. M.; Wattel, E. M.; Roorda, L. D.; Terwee, C. B. (Quality of Life Research, 2020)
Purpose: To develop and test the validity of a Patient-Reported Outcomes Measurement Information System (PROMIS®) short form for measuring physical function of geriatric rehabilitation patients.Methods: Experts selected items from the Dutch-Flemish PROMIS v1.2 Physical Function (PROMIS-PF) item bank and proposed new items to develop the PROMIS-PF short form for geriatric rehabilitation (PROMIS-PF-GR). Patients evaluated its content validity. Structural validity was assessed by evaluating unidimensionality (confirmatory, exploratory, and bi-factor analyses [criterion: Omega H > 0.80 and ECV > 0.60]), local independence (criterion: residual correlation < 0.20) ,and monotonicity (criterion: Hi-coefficient ≥ 0.30). Measurement invariance was assessed by evaluating Differential Item Functioning (DIF) between geriatric rehabilitation patients and people from the general population using ordinal logistic regression. Internal consistency was assessed by calculating Cronbach's alpha (criterion: alpha ≥ 0.70).Results: Experts selected 24 items from the PROMIS-PF item bank and proposed one new item which was not included in the short form. Patients considered the 24 items relevant and containing essential information. The PROMIS-PF-GR's psychometric properties were evaluated in 207 patients (mean age ± SD, 80.0 ± 8.3 year; 58% female). The 24 items were found to be sufficiently unidimensional (Omega H = 0.82, ECV = 0.70), locally independent (98.7% item pairs), and monotone (all ≥ 0.32). Five items were flagged for DIF, but their impact on the total score was negligible. Cronbach's alpha was 0.94.Conclusion: The PROMIS-PF-GR was developed from the PROMIS-PF and has good content validity, structural validity, measurement invariance, and internal consistency in Dutch geriatric rehabilitation patients. We recommend to confirm the content validity of the PROMIS-PF-GR in other countries.